Acquisition of iron and production of siderophores in Helicobacter pylori (b) (Sciences & Technologie. C, Biotechnologies, 2010)
Helicobacter pyloriis know to be an important etiological agent of chronic gastritis and peptic ulcer in human and also associated with gastric cancer. Iron acquisition plays an important role in bacterial virulence. In this study, H.pylori was cultured under iron restricted medium by using the iron chelating compound, 2.2’- dipyridyl to induce synthesis of possible siderophores and iron-regulated outer membrane proteins. Siderophores production was detected by chemical assays and all H.pylori strains tested were able to produce hydroxamate type siderophores, as revealed by Csaky test, for growth in low iron medium. Parallely, under these conditions, electrophoretic analysis by S.D.S. page detected the presence of protein with molecular weight of 74 KDa in all strains of H.pylori examined. This appeared to be iron-repressible outer membrane proteins , and might be specific receptor expressed only when the medium is deprived of iron. Also, the experiments of bioassays (feed Crossing) showed that there was an interchangeability of  iderophores between H.pylori strains tested, but these strains were unable to use exogenic siderophores.